The marginal profitability of the production's main factors in agricultural farms from Romania depending on the economic size - Raluca-Alexandra Rădoi; Manea Drăghici; Emilian Merce; Diana Maria Necula (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
The economic dimension of the agricultural farm is intensively studied both by agricultural specialists, who usually want farms as large as possible, but also by agrarian economists who measure the profitability of the factors involved in obtaining agricultural production at the scale of the economic dimension. In addition to established technicaleconomic indicators, such as: gross product, profitability, labor productivity, which show the overall efficiency of the factors, specific indicators are also used that show the separate efficiency of the factors through the marginal profitability, calculated with the help of elasticity coefficients. The paper used data provided by FADN- Eurostat, to calculate the elasticity of the capital and labor force, consumed in the agricultural holding, for the period 2007-2020, calculating the Cobb-Douglas production function. The coefficients of elasticity were calculated and compared for the six classes of economic size of the agricultural holding, from the South Muntenia Development Region, in order to draw conclusions regarding the profitability on capital and labor force, at the scale level. The authors aim to continue their studies with the analysis of elasticity coefficients at the level of the development regions of our country and their comparison with similar indicators from farms at the level of some regions of the European Union countries.
Keywords: D01; D24; 330; agricultural farm; coefficient of elasticity; Cobb-Douglas function; scale economy